Malignant transformation of abdominal wall endometriosis to clear cell carcinoma: case report - Gentil, João Kleber de Almeida; Migliore, Renato; Kistenmacker, Fábio Jorge Neubaner; Oliveira, Marcio Menezes de; Garcia, Rodrigo Biscuola; Bin, Fang Chia (São Paulo Medical Journal, 2018)
BACKGROUND: Malignant transformation of endometriosis in the abdominal wall is a rare and still poorly understood event. Less than 30 cases have been reported in the worldwide literature. Most cases of solid tumors are report in a previous abdominal scar with malignant transformation of a focus of endometriosis. Presence of lymph node metastases in nearby chains is frequent and is associated with poor prognosis. CASE REPORT: We report a case of a 42-year-old woman with a history of abdominal surgery (Pfannen- stiel) to resect abdominal wall endometriosis. Physical examination revealed a solid mass of approximately 10 cm x 6 cm in the anterior wall of the abdomen. Computed tomography (CT) of the abdomen and pel- vis showed a heterogeneous, predominantly hypoattenuating expansive formation measuring 10.6 cm x 4.7 cm x 8.3 cm. The patient underwent exploratory incisional laparotomy, block resection of the abdomi- nal mass and lymphadenectomy of the external and inguinal iliac chains. The abdominal wall was recon- structed using a semi-absorbable tissue-separating screen to reconstitute the defect caused by resection of the tumor. Histological evaluation revealed infiltration by malignant epithelioid neoplasia, thus confirm- ing the immunohistochemical profile of adenocarcinoma with clear cell components. Lymphadenectomy showed metastatic involvement of an external iliac chain lymph node. CONCLUSION: Resection of the mass along with the abdominal wall, with wall margins, is the most effec- tive treatment. Reconstruction is a challenge for surgeons. The patient has been followed up postopera- tively for eight months, without any evidence of disease to date.